MOTIVASI BERBUSANA ISLAMI DI KALANGAN MAHASISWA SEKOLAH TINGGI ILMU KESEHATAN (STIKES) ‘AISYIYAH SURAKARTA (TAHUN 2015) - Nazaruddin Latif (Universitas Muhammadiyah Surakarta, 2016)
This study aims to assess the perception, motivation, and factors supporting or inhibiting student STIKES 'Aisyiyah Surakarta wear Islamic dress. The method used was participant observation (observation participate) and indepth interviews (depth interview), made especially to students who have completed the Ma'had program. As a result, the perception of Islamic dress is dominated by the lack of proper understanding, whereas motivation OF Islamic dresing is dominated by the influence of the religious environment and the influence of parents who have a good understanding of Islamic teachings. It is at once a contributing factor, whereas a non-religious environment becomes the obstacle factor.